The Japan’s Award for PPIM UIN Jakarta - Thaha, Idris (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2011)
PPIM UIN Jakarta acted as an advisor for the Visiting Program for Pesantren Leaders held by the government of Japan. PPIM UIN Jakarta has a network with many pesantrens in Indonesia. Since 2002, PPIM is deliberately asked by the government of Japan's to select about 12 to15 kyais, nyais, religious teacher (ustad) from various modern, traditional, and salafi pesantrens in Indonesia to be sent to Japan. Until now, at least there are 90 kyais, nyais, and religious leaders who have been participated in the program. This year, PPIM recommends 17 names of pesantren leaders and religious teachers to the Embassy of Japan in Jakarta to be selected to participate in the program.DOI: 10.15408/sdi.v18i3.431